Inheritance of Local Cultural Values through Balahak Performances: A Case Study of Music in a Bridal Procession Performance in Siulak Mukai - Alrizka Hairi Dilfa; Agus Cahyono; Wadiyo Wadiyo; Udi Utomo (International Conference on Science, Education, and Technology, 2022)
The purpose of this study is to analyze Local Cultural Values ​​in Balahak Performances and how the form of inheritance of Local Cultural Values ​​through Balahak performances in Siulak Mukai. This research is qualitative with data collected through document study, observation, in-depth interviews, and FGD. Then the stages of data analysis through: data reduction, data display, drawing conclusions, for the validity of the data using triangulation techniques and discussions with colleagues. The findings of the study indicate that the Balahak Performance (Bride Procession) is an art performance that contains local cultural values, which then the process of the Balahak performance becomes a means of socializing and internalizing local culture which can be said to be cultural inheritance. There is a synergy between organisms and the environment in forming a Balahak show so that it can be said subtantively that Balahak is an Environmental-Based Performance. Therefore, the cultural values of ecological wisdom are inherited through elements in the Balahak Performance including Music, Song Verses, Pantun, Costum, Arena, Participants, Audience.